2003
DOI: 10.1039/b307012c
|View full text |Cite
|
Sign up to set email alerts
|

Superelectrophilic heterocycles: facile SNAr–SEAr couplings involving very weak carbon nucleophiles

Abstract: Superelectrophilic halonitro-2,1,3-benzoxadiazoles undergo remarkably facile carbon-carbon couplings with some electron-rich aromatics and heteroaromatics, affording quantitatively products exhibiting an intense visible absorption due to strong intramolecular charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…It remains the case that the most important finding of this work is the successful characterization of WM‐ 1 a by NMR. While it has long been postulated that S N Ar–S E Ar couplings between electron‐rich and electron‐deficient aromatics or heteroaromatics must involve the initial formation of a Wheland–Meisenheimer complex,22–24 only one example in which such an intermediate had a lifetime significantly sufficient to be observed spectroscopically has so far been reported8. Interestingly, this example deals with the reactivity of DNBF–‐a superelectrophilic structure—towards supernucleophilic 1,3,5‐tris‐( N , N ‐dialkylamino)benzenes 26 a – c as shown in Scheme 8.…”
Section: Resultsmentioning
confidence: 99%
“…It remains the case that the most important finding of this work is the successful characterization of WM‐ 1 a by NMR. While it has long been postulated that S N Ar–S E Ar couplings between electron‐rich and electron‐deficient aromatics or heteroaromatics must involve the initial formation of a Wheland–Meisenheimer complex,22–24 only one example in which such an intermediate had a lifetime significantly sufficient to be observed spectroscopically has so far been reported8. Interestingly, this example deals with the reactivity of DNBF–‐a superelectrophilic structure—towards supernucleophilic 1,3,5‐tris‐( N , N ‐dialkylamino)benzenes 26 a – c as shown in Scheme 8.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, so far only one system has been reported that addresses this question. Terrier and coworkers determined [21] a second-order rate constant of 5.88  -1 s -1 (MeCN, 25°C) for the reaction of 4,6-dinitrobenzofuroxane with azulene (1). From the electrophilicity parameter of this electrophile (E = -5.06) [20] and the N and s values of 1 given in Table 2, we calculated k 2 as 42.9  -1 s -1 at 20°C.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explain the above observation about reaction rates, one must take into account that (i) the benzofurazan ring has a stronger inductive effect and a lower resonance effect than a nitro group [50]; (ii) the combined result for the nitrobenzofurazan is a strong electron-withdrawing effect facilitating the S N Ar substitution; (iii) methoxy and aryloxy substituents appear to be better leaving groups than chloro; and (iv) there is a transition state leading to the immediate formation of a red-colored Meisenheimer complex 4 [51][52][53][54][55] and then, more slowly, to the substitution product 3 that is detectably fluorescent. One may assume that the basic AAs, which are more nucleophilic than all other AAs, prevail whenever the aryloxy group is not activated (2a) or deactivated by an electronwithdrawing formyl group (2d), even when there are methoxy groups (2e).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%